Re-Examining School Structures of People, Place, and Time to Promote Equity at the Middle Level - Katherine M Main; Dana Pomykal Franz; Kristina N Falbe; Cheryl Ellerbrock (Middle Grades Review, 2023)
In 2018 we published a chapter entitled “Middle Grades Schools and Structures” (Ellerbrock et al., 2018a) in Literature Reviews in Support of the Middle Level Education Research Agenda (Mertens et al., 2013). Building on the earlier work of Ellerbrock et al. (2018a), this chapter reviewed literature between 2000 and 2018 that reported on the organizational structures of middle level education settings in the United States of America and Australia. Though the findings highlighted the dearth of research specifically examining the organizational structures of middle level education, the literature examined supported the original three key interconnected themes of people, place, and time (Ellerbrock et al., 2018b) as being key features necessary for the implementation of effective middle schooling practices. In our conclusion, we called for more robust research in this area to guide policy and enact practices across different jurisdictions. At the same time, Bishop and Nagle (2018) noted the many increasing disparities in access to quality education and invited readers to consider how schools can serve all students both equitably and well. Equitable access is first and foremost, but equitable outcomes for all students is paramount. At the time of publication of all of these works, no one could have predicted the significant negative impact of COVID-19 and the resultant exacerbation of the already challenging inequities in education across the globe. However, research over the last five years, and particularly since 2020, has placed a greater focus on policy, system, and grassroots pedagogical changes to bridge this widening gap. In light of this heightened focus, this essay aims to reexamine the three key themes of people, place, and time and, when implemented with integrity, the ways middle grades schools and structures can contribute to creating both developmentally responsive and equitable educational experiences for young adolescent learners.
Keywords: middle school; equity; education; middle grades